Nanoparticles Interacting with Proteins and Cells: A Systematic Study of Protein Surface Charge Effects. Issue 2 (21st December 2013) - Shang, Li; Yang, Linxiao; Seiter, Jürgen; Heinle, Marita; Brenner‐Weiss, Gerald; Gerthsen, Dagmar; Nienhaus, G. Ulrich
<x xml:space="preserve">Abstract</x> Despite intense research on biological and biomedical applications of nanoparticles, our understanding of their basic interactions with the biological environment is still incomplete. Systematic variation of the physicochemical properties of the nanoparticles is widely seen as a promising strategy to obtain further insights. In view of the key role of the protein adsorption layer forming on nanoparticles in contact with biofluids, we systematically varied the surface charge of proteins adsorbing onto nanoparticles by chemical modification so as to examine the effect of Coulomb forces in modulating nano‐bio interactions. We chose human serum albumin (HSA) as a model protein and ultra‐small, negatively charged fluorescent gold nanoclusters (AuNCs) as model nanoparticles. By using fluorescence and CD spectroscopies, we measured binding affinities and structural changes upon binding of the HSA variants. The strengths of the protein‐nanoparticle interactions were found to change substantially upon modifying the surface charge of HSA. Furthermore, by using inductively coupled plasma optical emission spectroscopy, confocal fluorescence microscopy, scanning transmission electron microscopy and cell viability assays, we observed that cellular interactions of the AuNCs, including their adherence to cell membranes, uptake efficiency and cytotoxicity, depended markedly on the different surface charges of the HSA variants adsorbed onto the nanoparticles. These results illustrate vividly that the cellular responses to nanoparticle exposure depend on the specific properties of the proteins that adsorb onto nanoparticles from biofluids.